January protests shutdown (Kazakhstan) - Voidly (2022)
CRITICAL severity censorship detected in Kazakhstan. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: KZ-2022-0001
Keywords: censorship; KZ; censorship; critical